PROBLEM BASED LEARNING IN IMPROVING LEARNING OUTCOMES IN ISLAMIC RELIGIOUS EDUCATION AND LEARNING MOTIVATION - Rokhmad Afif; Mukh Nursikin; Nur Kholifah; Shokhibul Mighfar (Fakultas Tarbiyah, Universitas Ibrahimy, 2025)
This study aims to determine the effectiveness of the problem-based learning method in PAI learning on improving learning outcomes and learning motivation of students of SMK Ma'arif Walingoso Kajoran. This research uses an experimental method with a quasi experimental design approach. This research was conducted at SMK Ma'arif Walisongo Kajoran. The instruments used in this study were learning outcome scales and learning motivation. Data analysis techniques using Wilcoxon test and Mann Whitney test. Based on the results of the Wilcoxon test, it shows that problem-based learning (PBL) method has an effect on improving student learning outcomes in the experimental group and in the control group with lecture techniques there is no difference. While the results of the Wilcoxon test of learning motivation, there is a difference in learning motivation in the problem-based learning method and there is no difference in the lecture technique. Problem-based learning (PBL) method in PAI learning is effective in improving learning outcomes and learning motivation in students of SMK Ma'arif Walisongo Kajoran.